[OP.2B.03] GLOMERULAR HYPERFILTRATION AS A RISK FACTOR FOR RENAL IMPAIRMENT AND HYPERTENSION IN APPARENTLY HEALTHY SUBJECTS. (September 2016) - Vrdoljak, A.; Ivkovic, V.; Karanovic, S.; Dika, Z.; Domislovic, V.; Dapic, K.; Gallineo, L.; Ivandic, E.; Josipovic, J.; Vukovic, I.; Kos, J.; Laganovic, M.; et al.
Abstract : Objective: Chronic kidney disease(CKD) is established CV risk factor, and already early renal impairment(RI) increases risk for hypertension(HT) and loss of renal function. It was reported that blood pressure (BP) and metabolic derangements are associated with glomerular hyperfiltration(GHF), and GHF increases risk of developing microalbuminuria (MA) in HT stage 1. Our aim was to analyze whether GHF predicts progression to HT and RI in apparently healthy subjects. Design and method: Out of 954 subjects enrolled in ENAH follow-up study, 371 (137 m, 234 w; mean age = 46 years) were eligible for further analysis:100 with optimal, 72 with normal BP, 70 with PHT (high normal BP), and 129 with newly diagnosed untreated HT. Follow-up period was 77 ± 12 months. Exclusion criteria were treatment with antihypertensive drugs, diabetes, pregnancy, eGFR<60 ml/min, CV or cerebrovascular incident, chronic terminal diseases, dementia, immobility and missing data. BP and heart rate were measured using Omron 6 device following the ESH guidelines. Uric acid, glucose, lipids, serum creatinine, hsCRP, leptin and adiponektin were determined; HOMA index was used to calculate insulin resistance and MDRD formula to estimate GFR. Albumin to creatinine ratio (ACR) was determined from the first morning spot urine. GHF was defined as eGFR above the cut off value of the 5th quintile of the whole group. Results: In the GHF group eGFR(ml/min/year) decreased significantly more than in others (−3.4 (IQ−5.8 to −1.76 vs. −1.5 (IQ−2.6 to −0.3); total decrease −17.7% vs. −9.8%; per year −2.8% vs. −1.5%; all p < 0.001). ACR was non-significantly higher in GHF group at enter and at the end of follow-up (5.73 (IQ3.35–8.6) vs. 4.5 (IQ3.31–7.25); p = 0.06, 5.93 (IQ4.26–8.64) vs. 5.7 (IQ4.08–9.82; NS, respectively). In the GHF group, at the end of follow-up ACR did not increase significantly. At enter and at the end of follow-up BP was significantly lower in GHF group (p < 0.001). At the end of study we failed to observe difference in increase of BP and new-onset HT between GHF and others. Conclusions: In our group of healthy subjects GHF was associated only with more rapid decrease of GFR. No impact of GHF on ACR increase and development of new-onset HT in healthy subjects was observed. GHF has less prominent effect on HT and kidney function in apparently healthy subjects than in those with HT and metabolic disorder.